Understanding Adult Learning in Higher Education from African Philosophy of Education and Transformative Perspectives - Majani, William Pastory (Papers in Education and Development, 2021)
This paper exposes perspectives that advocate for learning that builds on two main aspects, that: adult learning involves meaning- making processes that acknowledge the dialectical relationship between the self and society within the experiences of learning and; adult learning is transformative and emancipatory at both individual and community level. Within the African philosophy of education and transformative strands, adult learning is informal, non-formal and formal. This context calls for innovative teaching and learning that are sensitive to diverse ways of learning. While it is essential to orient adult learners to think critically and act reflectively as they prepare for work, it is also vital to ensure that what they learn fosters their personal and societal transformation. Overall, this implies that adult learning ought to include the spiritual, biological, intellectual and the emotional dimensions of learning. Keywords: adult learning, higher education, spirituality, transformative education, whole learning